Toronto Sprawls : A History - Solomon, Lawrence, 1948- (Book collections on Project MUSE., 2007)
"Toronto Sprawls makes a convincing case that urban sprawl in Toronto was caused not by market forces, but rather by policies and programs designed to disperse Toronto's urban population."--Jacket